Penguatan Literasi Pencegahan Fraud Bagi Guru, Tenaga Kependidikan, Dan Siswa di SMAN 2 Pekalongan - Anissatus Sholihah, Ria; Cahyo Kurniawan, Pratomo; Salamah, Rizqi (Jurnal Pengabdian Masyarakat Akademisi, 2025)
Fraud prevention literacy in schools plays a crucial role in shaping ethical behavior and financial integrity from an early age. It is essential to educate students and school personnel about the risks of fraud and strategies for prevention within the school environment. By integrating fraud literacy into the curriculum, schools can foster a culture of transparency, accountability, and integrity. The methods used include exploring programs aimed at raising awareness of fraud, implementing anti-fraud initiatives, providing training for educators, and leveraging technology in fraud detection. Additionally, another focus of discussion is the long-term benefits of incorporating fraud prevention education in schools, which contributes to the development of a more ethical and financially literate society.